Neglected adult PFAPA syndrome - Aiping Zhang; Ruifeng Zhang; Yiling Jiang; Ling Shi; Meihong Luo (Radiology Case Reports)
Periodic Fever, Aphthous stomatitis, Pharyngitis and cervical Adenitis (PFAPA) syndrome is rarely seen in adults. The diagnosis is challenging, and the majority of cases are misdiagnosed early. Here we present a case of a 69-year-old woman with PFAPA syndrome, initially misdiagnosed as pharyngitis or lymphadenitis and received multiple antibiotic therapy without any clinical benefit. This report emphasizes the importance of early identification of the disease. Patients with periodic fever accompanied by cervical lymphadenitis, clinicians should consider the possibility of PFAPA syndrome especially when antibiotic treatment is ineffective. The case showed that colchicine could significantly prolong the interval between fever, with the longest interval reaching 8 months, which significantly improved the patient's quality of life (QOL).